Strain analysis on Ti1-xAgx and Ag-TiNx electrodes deposited on polymer based sensors - Marques, S. M. (2016)
Electroactive polymers are among the most interesting class of polymers for sensors and actuators applications in the biomedical field, including as the area of smart prosthesis. Appropriate suitable electrodes can be produced from Ti based coatings with added tailored multifunctional properties as biocompatible properties, to acquire and/or apply the electrical signal from/to the piezoelectric material. Further, the thin films themselves can be used as piezoresistive materials. This work reports on a piezoelectric polymer coated with different conductive thin films an on the electrical resistance variation of the thin films during uniaxial mechanical stretching up to 5% of strain. The electrodes are based on Ti1-xAgx and Ag-TiNx, deposited by d. c. and pulsed magnetron sputtering at room temperature on piezoelectric -phase poly(vinylidene fluoride), PVDF. an excellent piezoelectric polymer. It is concluded that deposited thin films show piezoresistive properties, which increase with increasing applied strain and reaching gauge factors (GF) up to 700. All thin films deposited on β-PVDF exhibit a similar behavior with respect to the electro-mechanical properties, the GF increasing with increasing strain and being larger in the plastic zone than in the elastic one. The Ag-TiNx samples show highest GF values among all prepared thin film compositions.